Tabela de vida de Tetranychus neocaledonicus (ACARI: Tetranychidae) em coqueiro anão-verde e suscetibilidade dos seus híbridos - Soares, Janice da Silva (2024)
Tetranychus neocaledonicus André (Acari: Tetranychidae), known as the red spider mite, is an emerging pest of coconut palms in Brazil and can cause significant damage, especially in new plantations. The green dwarf coconut, Cocos nucifera, is the predominant cultivar in commercial plantations in Brazil. However, studies have not been conducted on the susceptibility of coconut palms to red spider mite. Therefore, the objective of this study was to evaluate the susceptibility of the green dwarf variety and the hybrids of dwarf × tall coconut palms, developed by the Embrapa breeding program, to T. neocaledonicus. The susceptibility of the green dwarf coconut was assessed using a life table approach, starting with T. neocaledonicus eggs of known age. Immature stages were evaluated twice daily, and the adult stage once per day. The susceptibility of the hybrids was assessed through growth rate and preference tests. The instantaneous growth rate (ri) of T. neocaledonicus was estimated in the laboratory on leaflets collected from 16 dwarf × tall hybrids cultivated in the experimental field of Embrapa Tabuleiros Costeiros, in Itaporanga d’Ajuda, Sergipe. Preference for contrasting hybrids, where the mites exhibited the highest and lowest ri values, was evaluated in two-choice arenas at 1, 24, 48, and 72 hours. All experiments were conducted in the laboratory, at a temperature of 27 °C ± 2 °C, 90% humidity, and a 12-hour photoperiod. Regarding biological aspects, the average life cycle of female and male T. neocaledonicus on green dwarf coconut was 13.02 and 11.69 days, respectively. For females, the larval, protonymph, and deutonymph stages lasted 2.22, 2.51, and 2.13 days, respectively; while for males, these stages lasted 1.88, 2.18, and 1.71 days, respectively. The sex ratio was 0.61. The life table parameters observed were net reproductive rate (R0) of 10.57 ♀/♀, mean generation time (T) of 20.03 days, finite rate of increase (λ) of 1.12 ♀/♀, and intrinsic rate of increase (rm) of 0.12 ♀/♀/day. For the hybrids, the growth rate of T. neocaledonicus differed among treatments, with the highest rate recorded in hybrid 9 and the lowest in hybrid 16. However, T. neocaledonicus exhibited no preference among the contrasting hybrids. T. neocaledonicus develops well on green dwarf coconut, confirming the potential of this mite to cause damage to commercial coconut plantations. Furthermore, the contrasting hybrids exhibited different levels of susceptibility and resistance to T. neocaledonicus, as shown by the instantaneous growth rate. Additional studies in the field and in the laboratory should be conducted to confirm these findings.